Trends in Stem Cell Biology and Technology - Baharvand, Hossein; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2009)
The study of stem cell research has recently gained the attention from a growing, multidisciplinary community of scientist; this exponential growth of interest is driven by the hope of discovering cures for several diseases through transplantation medicine. Trends in Stem Cells Biology and Technology aptly serves this developing community as it reveals new aspects of stem cell research by specifically covering studies focused on spermatogonial stem cells, uniparental embryonic stem cell lines, the generation of gametes from stem cells, reprogramming germ cells to stem cells, nuclear and somatic cell genetic reprogramming, tissue engineering and mechanotransduction of stem cells and finally the development of stem cell technologies for the treatment of deafness, heart disease, corneal injury and diabetes. With contributions by leading scientists and renowned scholars, Trends in Stem Cells Biology and Technology offers a wide audience cutting edge information at a crucial time in this ever expanding field.
Human Embryonic Stem Cells: Their Nature, Properties, and Uses -- Production of Uniparental Embryonic Stem Cell Lines -- Parthenogenetic Embryonic Stem Cells in Nonhuman Primates -- Nuclear and Somatic Cell Genetic Reprogramming -- Reprogramming Male Germ Cells to Pluripotent Stem Cells -- Pluripotent Stem Cell Epigenetics During Development and Cancer -- Observing and Manipulating Pluripotency in Normal and Cloned Mouse Embryos -- Current Developments in Genetically Manipulated Mice -- Differentiating Gametes from Stem Cells -- Spermatogonial Stem Cells -- Regulated Transcripts and Coregulated microRNAs in Male Spermatogonial Stem Cells -- Human Mesenchymal Stem Cells: Basic Biology and Clinical Applications for Bone Tissue Regeneration -- Clinical Cell Therapy for Heart Disease -- Embryonic Stem Cells, Cardiomyoplasty, and the Risk of Teratoma Formation -- Neural Differentiation of Human Embryonic Stem Cells and Their Potential Application in a Therapy for Sensorineural Hearing Loss -- Stem Cell Transplantation Supports the Repair of Injured Olfactory Neuroepithelium After Permanent Lesion -- Strategies Toward Beta-Cell Replacement -- Corneal Epithelial Stem Cells and Their Therapeutic Application -- Tissue Engineered Scaffolds for Stem Cells and Regenerative Medicine -- Mechanotransduction and Its Role in Stem Cell Biology.
Keywords: Life sciences; Biotechnology; Cell biology; Biomedical engineering; Life Sciences; Cell Biology; Biotechnology; Biomedical Engineering; Electronic books